EVALUASI KESESUAIAN LAHAN UNTUK TANAMAN PINANG (Areca catechu) DI DAS REMU, SORONG , PAPUA BARAT - Fernando D. Korwa; Jailani Husain; Tilda Titah; Joice Supit (Universitas Sam Ratulangi, 2016)
ABSTRACTThe purpose of this study was to determine the land suitability for areca nut (Areca catechu) in Remu watershed, Sorong, West Papua Province. This research uses descriptive method comprising of survey and map overlay. This research was conducted in the field and the GIS laboratory, Faculty of Agriculture, University of Sam Ratulangi. The research was conducted during Â± 4 months, namely from January to April 2015. It was revealed that within 5771.74 ha of suitable area, 2581.76 ha area was classified as the most suitable, 898.7 ha as fairly suitable, and 1730.57 ha as marginally suitable. In addition, 509.78 ha area was evaluated as presently not-suitable and 50.93 ha as permanently not suitable. Further study is required as to provide more specific site information on land suitability for areca nut in the study area.Keywords : GIS, land suitability, areca nut